Classroom reading inventory - Silvaroli, Nicolas J. (McGraw Hill, 2001)
This trusted reading inventory resource is ideal for pre-service and in-service teachers who use an informal reading inventory test to help identify students' reading problems. A classic in the field, it is the leading reading inventory text, brief and easy to use in a consumable, spiral-bound format. The CRI (Classroom Reading Inventory) is specially prepared for in- and pre-service teachers who have little or no experience with informal reading inventories. It is designed to be administered in fifteen minutes or less.